Influence of ultra-processed foods consumption during pregnancy on baby's anthropometric measurements, from birth to the first year of life: a systematic review - Cristianny Miranda; Rafaela Cristina Vieira e Souza; Luana Caroline dos Santos (Instituto Materno Infantil de Pernambuco, 2021)
Abstract Objectives: to perform a systematic review of studies that investigated the influence of ultra-processed foods (UPF) consumption during pregnancy on child's anthropometric parameters up to one year of life. Methods: cohort and cross-sectional studies were researched in BVS, Cinahl, Cochrane, Embase, Pubmed, Scopus and Web of Science databases until March 2020, and the main descriptors were: "Pregnant Women", "Ultra-processed foods", "Birth Weight", "Smallfor Gestational Age", "Infant", "Newborn". Results: seventeen articles were considered eligible and evaluated the associations between the exposures: ultra-processed dietary patterns; soft drinks, sugar-sweetened beverages, artificially sweetened beverages; fast food, junk food, sweets, snacks and the outcomes: birth weight and its classifications; length and head circumference at birth; birth weight adjustments according to gestational age; weight/age, length/age, body mass index/age and weight/length indices. The results showed: 36 non-significant associations between the exposures and the outcomes; 13 direct associations (outcomes versus ultraprocessed dietary patterns, soft drinks, artificially sweetened beverages, sweets, junk food) and 5 inverse associations (outcomes versus ultra-processed dietary patterns, soft drinks). Conclusions: most of the evaluated literature did not demonstrate the influence of UPF consumption during pregnancy on the newborn's anthropometric measurements up to one year of life and denoted a smaller number of direct and inverse associations between the exposures and the outcomes.